Illuminae: Illuminae Series #1 - Kaufman, Amie; Kristoff, Jay (New York : Alfred A. Knopf, 2015)
"The planet Kerenza is attacked, and Kady and Ezra find themselves on a space fleet fleeing the enemy, while their ship's artificial intelligence system and a deadly plague may be the end of them all"--
Keywords: Interplanetary voyages -- Fiction; Artificial intelligence -- Fiction; Plague -- Fiction; Science fiction